Ag-Incorporated Polydopamine/Tannic Acid Coating on Titanium With Enhanced Cytocompatible and Antibacterial Properties - Zhang, Hao; Shen, Xiaolong; Fei, Zhikui; Fan, Xingping; Ma, Lan; Wang, Haibo; Tian, Congxue; Zhang, Bo; Luo, Rifang; Wang, Yunbing; Huang, Shengtian (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium (Ti) and its alloys are the most commonly used materials for bone implants. However, implant failure often happens due to bacterial infection. Developing antibacterial coatings on Ti implants is an effective strategy. Dopamine and tannic acid were cross-linked to form coating on Ti through Michael addition and Schiff base reaction. In addition, the Ag ions were grafted on the coating by the redox reaction of phenolic hydroxyl groups. Thus, an Ag-incorporated polydopamine/tannic acid coating was prepared on Ti substrate. SEM, EDS, water contact angle, FTIR, and XRD results demonstrated that the coating was formed on Ti successfully. The antibacterial activity of the coating against Gram-negative E. coli was examined, and the cytotoxicity of the coating was investigated by mouse fibroblast cells. The improvement of hydrophilicity, good cytocompatibility, and antibacterial effectiveness indicates that the coating has potential to surface modification of Ti implants.